Marginal Stockholders and Implied Tax Rates - Brooks, LeRoy D.; Edwards, Charles E. (The Review of Economics and Statistics, 1980)
In this REVIEW some years ago, Edwin Elton and Martin Gruber (1970) used the concepts of market equilibrium and differential tax rates between capital gains and dividend income to structure a theoretical model which they then used empirically to estimate marginal stockholder tax rates. Their specification of an equilibrium condition is appropriate for a security seller who qualifies for preferential tax treatment of capital gains. However, their assumption that such a stockholder is the marginal stockholder in a market equilibrium is questionable. This assumption, along with disregard of transactions and other costs, is essential to their empirical derivation of stockholder tax rates. This note presents an alternative explanation of their empirical results.